Effect of Different Ceramic Waste Powder on Characteristics of Fly Ash-Based Geopolymer - Bernardinus Herbudiman; Subari Subari; Bactiar Nugraha; Indah Pratiwi; Asnan Rinovian; Euneke Widyaningsih; Evi Dwi Yanti; Bagus D. Erlangga; Jakah Jakah; Seto Roseno (Civil Engineering Journal, 2024)
The escalating demand for construction materials driven by rapid population growth has heightened the reliance on cement binders, resulting in increased CO2 emissions from the cement industry. Geopolymers, considered environmentally friendly alternatives, have been explored in various studies to address this challenge. This research specifically investigates the impact of different types of ceramic waste bricks (BT), floor tiles (FT), roof tiles (RT), and sanitary ceramics (ST) on the physical and mechanical properties of fly ash-based geopolymer mortar. To provide a comprehensive understanding, this research examines the compressive strength, mineral phase, chemical bonds, and microscopic evolution of fly ash geopolymer mortar incorporating varying proportions of each ceramic waste type (25% and 50% fly ash replacement). A consistent mixture of Na2SiO3and NaOH was used for the alkaline solution in all formulations. The curing process was carried out at room temperature for 7, 14, and 28 days prior to the compressive strength test. The result revealed that the inclusion of 25% BT experienced higher strength compared to the control sample after 14 days, but the strength became comparable after 28 days at 40.24 MPa. A reduction in strength was evident with the addition of other ceramic components. Moreover, higher incorporation of CWP correlated with a faster setting time for fresh geopolymers. This was also linked to the degree of gel formation, as indicated in the microstructure images. The emergence of plagioclase minerals was evident in all formulations of the geopolymer products under XRD analysis, while the bond of the geopolymer signature, Si-O-T (T = Si or Al), was identified from the infrared spectra. The microstructure of the binder showed a geopolymer matrix alongside unreacted fly ash particles. Overall, CWP replacement up to 25% can be potential in fly ash geopolymer without sacrificing significant strength loss and remaining in the range of normal strength mortar. Doi: 10.28991/CEJ-2024-010-02-06 Full Text: PDF